Natural disasters and sustainable housing requirements in Libya-The case of Daniel Tornado in Derna - Abu Aziza, Salah; Boudjemaa, Khalfallah (Technium Sustainability, 2024)
Natural hazards, such as valley floods and hurricanes, constitute one of the types of environmental crises in modern times, as a result of the population’s encroachment on existing urban regulations and plans, which produces residential complexes that lack the rules of systematic planning and the requirements of balanced sustainable development. In this research, we will discuss the effects of Hurricane Daniel on the city of Derna, overlooking the Mediterranean Sea in eastern Libya, which was subjected to a storm that left thousands of victims and caused floods that swept away large parts of the city, being the largest natural disaster to have struck the country. Libya was often exposed to natural hazards, as agreed upon by references in paleoclimatology and the history of the region. In 1941, the Derna Valley was subjected to a major flood that submerged parts of the city and swept German military vehicles into the sea. During the period between 1959 and 1969, the region was exposed to several similar incidents that left hundreds of victims, which confirms that it is a dangerous region in terms of natural disasters. We will also determine the arrangements required to achieve sustainable housing that ensures the necessary conditions for embodying a safe built environment, including the organization of urbanization that takes into account the natural and Social and economic development, and integrating climate diversity according to the features of the National Housing Policy between 2014-2033 (Ministry of Housing and Utilities, 2013). The illegal overuse of available natural resources, especially real estate, to the point of depletion, and failure to respect the rules of prevention and security, leads to... “This leads to the establishment of unsustainable residential complexes that are constantly exposed to risks.” ( Julian gargani, 2016).